1998
DOI: 10.33584/jnzg.1998.60.2307
|View full text |Cite
|
Sign up to set email alerts
|

Long-term fertiliser application and fertility of hill soils

Abstract: Application of phosphatic fertiliser to legume/grass pastures, and increased stocking rate, is commonly assumed to increase soil organic matter (estimated from soil carbon) content, to lower soil pH, and to increase soil Olsen P status. Changes in these variables in soils derived from sedimentary parent material were monitored over 16 years, in a longterm grazing experiment on southern North Island hill country. There were 2 fertiliser treatments, principally high (capital applications followed by 375 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The magnitude of such losses suggests that, rather than being at steady state, the soil organic matter (SOM) content in developed pastures continues to change in response to the balance of inputs and losses. Earlier work by Ghani et al (1996) and Lambert et al (1998) also found losses in SOC in pasture soils that would otherwise be regarded as still developing and accumulating SOC. It is important to consider the consequences of losses of SOC of the magnitude reported by Schipper et al (2007).…”
Section: Introductionmentioning
confidence: 85%
“…The magnitude of such losses suggests that, rather than being at steady state, the soil organic matter (SOM) content in developed pastures continues to change in response to the balance of inputs and losses. Earlier work by Ghani et al (1996) and Lambert et al (1998) also found losses in SOC in pasture soils that would otherwise be regarded as still developing and accumulating SOC. It is important to consider the consequences of losses of SOC of the magnitude reported by Schipper et al (2007).…”
Section: Introductionmentioning
confidence: 85%
“…Long-term trials undertaken in New Zealand hill country support the fact that SOM can be increased with fertiliser application (Lambert et al 1996;Parfitt et al 2003). When the plots were grazed hard, however, SOM was lost -more from the high-fertiliser plots than the low-fertiliser plots due to increased activity of soil decomposers, but SOM was still higher on the high-fertiliser plots (Lambert et al 1998), as found in the Khan et al (2007) research.…”
Section: Soil Carbon/organic Mattermentioning
confidence: 59%